The Practice of the Presence of God: Theology as a Way of Life - Laird, Martin (Taylor and Francis, 2016)
Half Title -- Title Page -- Copyright Page -- Contents -- List of contributors -- Preface -- Acknowledgements -- Introduction. Oracles, prophets, and dwellers in silence: Hints of the 'pati divina' in the theology that is being birthed -- Notes -- Part 1 Foundational soundings -- 1 Theology as a way of life -- 1. -- 2. -- Notes -- 2 Undergoing something from nothing: The doctrine of creation as contemplative insight -- 1. Systematic theology and the way of unknowing -- 2. On not being 'two': Discovering creatio ex nihilo -- 3. Undergoing something from nothing -- 4. Love without a why -- Notes -- 3 The Trinity as our ascetic programme -- Notes -- Part 2 Personal accounts of a theological life -- 4 Ecumenical confessions of an unconventional Protestant -- Theology as a way of life -- The practice of the presence of God -- Ecumenical confessions of an unconventional Protestant -- Scripture -- Common lectionary -- Fellowship and communion -- Hymn-singing -- Notes -- 5 Augustine on practicing the presence of God -- I. -- II. -- III. -- IV. -- V. -- VI. On practising the presence of God -- Notes -- Part 3 Theological and liturgical retrievals -- 6 The liturgy, icons and the prayer of the heart -- Notes -- 7 To feel so as to understand: Hadewijch of Brabant and the legacy of St. Anselm -- Introduction -- 'My soul, be watchful -- my wretchedness, rouse yourself': Anselm and the problem of affective rectitude -- 'Why do I not experience what I have found?': Anselm's Proslogion -- 'I am scarcely aware of my sins': Compunction, contrast and the imagination in The Prayers and Meditations. -- Hadewijch of Brabant and the Anselmian legacy -- Conclusion -- Notes -- 8 Etching the ineffable in words: The return of contemplation to theology -- Introduction -- St. Gregory the Theologian and the ocean's calm